(untitled) (Journal of Dhaka Medical College, 2021)
Introduction: Carpal tunnel syndrome (CTS) is a clinical syndrome that results from compression of median nerve within the carpal tunnel at the wrist. The aim of this study was to review the clinical and demographic characteristics and electrophysiological patterns of CTS patients who presented to a tertiary care hospital in Bangladesh. Methodology; A descriptive cross-sectional study was conducted on 150 CTS patients at the neurology department, Dhaka Medical College Hospital between January, 2019 to March , 2020 . All the subjects had clinical evaluation and standardized nerve conduction studies of upper limbs (300 limbs) using the same protocol. Results: 228 hands were found to have clinical and electrophysiological features consistent with CTS. There was female predominance (90%) and the highest occurrence of CTS was in the 45-55 years age group. Bilateral CTS was found in the majority of cases ie 78 (52%) and the rest had unilateral CTS. Among those with unilateral CTS, right hand was affected more (41, 57%) than left hand (31, 43%). Most of the cases were idiopathic. Neurophysiological studies showed most patients had mild CTS (121 hands, 53%). Most of the cases were idiopathic (102, 68%). Where a risk factor was found diabetes was commonest one (32) followed by hypothyroidism (12) and pregnancy (4). Conclusion: There was marked female predominance and the 45-55 years age group was predominantly affected. Majority of cases had mild CTS. Bilateral involvement was more common. Right hand was more affected than the left hand. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 96-99